Electron Rephasing in a Laser-Wakefield Accelerator - Guillaume, E; Döpp, A; Thaury, C; Ta Phuoc, K; Lifschitz, A; Grittani, G; Goddet, J-P; Tafzi, A; Chou, S W; Veisz, L; Malka, V (Physical review letters, 2015)
An important limit for energy gain in laser-plasma wakefield accelerators is the dephasing length, after which the electron beam reaches the decelerating region of the wakefield and starts to decelerate. Here, we propose to manipulate the phase of the electron beam in the wakefield, in order to bring the beam back into the accelerating region, hence increasing the final beam energy. This rephasing is operated by placing an upward density step in the beam path. In a first experiment, we demonstrate the principle of this technique using a large energy spread electron beam. Then, we show that it can be used to increase the energy of monoenergetic electron beams by more than 50%.